‘Far Away Days’ or ‘Far Distant Days’? Assessing Translation Acceptability in Corpus of Contemporary American English (COCA) and British National Corpus (BNC) - Karjo, Clara Herlina (Bina Nusantara University, 2014)
Translating Indonesian reduplications into English is not an easy matter due to the difference in morphological form, syntactic function and semantic meaning of reduplications in both languages. For example, the phrase ?jauh-jauh hari? cannot be translated into ?far-far day?. This translation is not acceptable since it follows exactly the form of the original text, or only focusing on the morphological form, while the other two factors are disregarded. Thus, in assessing the acceptability of the translation, those three factors should be considered. However, the acceptability of the translation can also be checked by comparing the translations with the corpus. This article analyzes the translations of 3 Indonesian reduplications by 50 university students and compares their translations with similar expressions found in COCA and BNC to find out the degree of acceptability of the translations. The results show which translations are acceptable and which are not based on the frequency of usage.